Exploring the Role of Mindfulness as a Potential Self-Management Strategy for Physiotherapy Students when on Clinical Placement - Thomson, Di; Gowing, Francesca; English, Michael; Hassenkamp, Anne-Marie (International Journal of Practice-based Learning in Health and Social Care, 2017)
Healthcare programmes tend to neglect exploring self-care strategies for students whilst they are on their clinical placements. There is evidence that students experience placements as challenging because of the long hours, and endeavouring to meet the needs of many patients across diverse challenging settings. Mindfulness is a potential self-management strategy to enable students to manage the challenges and resultant stress during these times, and to work optimally within their competences. This study explores the role of mindfulness in attempting to meet these challenges. Purposive sampling was used to recruit nineteen MSc pre-registration physiotherapy students who received a two-hour mindfulness intervention prior to commencing their placement, and were encouraged to practice mindfulness for 30 minutes three times a week with a CD whilst on placement or in their own time. Additionally, they were asked to practice for 10-15 minutes ‘mindfulness of the breath’ during this period. A qualitative approach that incorporated thematic analysis was used to analyse the audio-recorded and transcribed pre- and post-placement focus groups. Perceived benefits from practising mindfulness were: a lessening of intrinsic stress, and an ability to cope with extrinsic stress with increased clarity and objectivity. The CD proved burdensome amongst the students, largely owing to time constraints, but this did not deter their desire to implement mindfulness during this time, and they devised alternative and individual modes of practicing this mind-body-based approach. This study lends evidence to support inclusion of mindfulness into the physiotherapy curriculum as a self-management strategy to empower students to cope with clinical placement associated stress.